TACTICS OF INSPECTION OF INDIVIDUAL OBJECTS AFTER EXPLOSION (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
This article discusses the tactical aspects of inspecting individual objects after an explosion. In this, the specific aspects of the inspection of the building where the explosion occurred, the open area, and the vehicle were analyzed.Also, the procedure for comprehensive inspection of the objects where the explosions took place, issues of the tactics of inspection of the explosion site will be considered. In addition, the use of technical means at the place of the explosion, the issues of formalizing the inspection process of taking samples were analyzed.